Management System Excellence in Manufacturing and Service Industries: MSME (Micro, Small, and Medium-Sized Enterprises) Sector in Bangalore - B, Rajesh (Global journal of Business and Integral Security, 2024)
Globally, management systems standards have helped many organizations adhere to the commonly accepted practices in business operations, resulting in increased growth and productivity and significantly higher customer satisfaction and retention. Apart from benefiting from the qualification of business, opening opportunities to enter organizations or markets that require certification is the prerequisite to conducting the business. This thesis will study the management system excellence – implementation and sustenance of management systems in manufacturing and service industries' MSME (micro, small, and medium-sized enterprises) sector in Bangalore and its impact on business. With the challenge of low literacy, unskilled workforce, limited resources, multiskilling, unorganized processes, and budget restrictions, this research project will oversee how the enterprises have managed still implement the management system; it will show the challenges the top management/business leaders faced, their choices and decisions as well as lessons learned. The study results and learnings will give confidence and hope and help implement and sustain such management systems in all MSME industries in the future. Bangalore is a hub of opportunities, and this study focuses on how management systems can assist the MSME industries to excel in their business operations. Research, Surveys, Discussions, and interviews were conducted using online tools and in-person discussions with individuals working in distinct roles within the MSME organization. Management system excellence in implementation and sustenance assists organizations to impact both their operations and business prospects as it gives them the eligibility for various prerequisites applied in business opportunities that are managed by MSME, and in general there are numerous benefits in a management system, such as •establishing business rules. •enabling a governance framework. •practical policy setting. •less miscommunication. •thoughts on succession planning. •transitional management. •focus on marketing. •Prerequisites in government contracts. •satisfying client requirements. •enabling due diligence. •systematic way for business review. •knowledge management. •documentation management. •resource management.